Possible signal of tropospheric circulation patterns in middle atmosphere dynamics, Collm (51.3°N, 13°E) mesosphere lower thermosphere winds: 1979 - 2008 - Jacobi, Christoph (Universität Leipzig, 2009)
Time series of monthly mean Collm mesosphere/lower thermosphere winds 1979 - 2008 are analyses with respect to a possible correlation with North Atlantic Oscillation (NAO) and Southern Oscillation (SO) indices. There is a positive correlation with both indices until the middle 1990s, but later the correlation decreases or even reverses. Owing to the coupling of the SO with the NAO the change of correlation occurs broadly at the same time. The change of correlation is probably connected with changes of the middle atmosphere mean dynamics. Zeitreihen von Monatsmittelwerten des Windes in der Mesosphäre/unteren Thermosphäre über Collm werden auf mögliche Korrelationen mit der Nordatlantischen Oszillation (NAO) und der Südlichen Oszillation (SO) hin untersucht. Während eine positive Korrelation bis in die 1990er Jahre existiert, schwächt sich diese in der Folge ab und kehrt sich teilweise um. Da NAO und SO gekoppelt sind, erfolgen diese Änderungen etwa zur selben Zeit. Die Änderung der Kopplung steht wahrscheinlich in Verbindung mit einer generellen Änderung der Dynamik der mittleren Atmosphäre.